2023
DOI: 10.3390/foods12040809
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Biologically Active Compounds from Stinging Nettle Leaves Part II: Processing of Exhausted Plant Material after Supercritical Fluid Extraction

Abstract: Stinging nettle (Urtica dioica L.) is one fantastic plant widely used in folk medicine, pharmacy, cosmetics, and food. This plant’s popularity may be explained by its chemical composition, containing a wide range of compounds significant for human health and diet. This study aimed to investigate extracts of exhausted stinging nettle leaves after supercritical fluid extraction obtained using ultrasound and microwave techniques. Extracts were analyzed to obtain insight into the chemical composition and biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Otles and Yalcin analyzed phenolic compounds in root, stalk, and leaves. The authors reported the lack of gallic acid and catechin in analyzed parts of the plant [ 63 ], which is in agreement with other studies [ 16 , 17 ] but contrary to other studies that reported the presence of only gallic acid [ 11 , 64 ] or both compounds [ 19 , 61 ]. The results showed that leaves were the richest in polyphenolic compounds, followed by stalk and root [ 63 ].…”
Section: Phenolic and Polyphenolic Compounds In Stinging Nettlesupporting
confidence: 88%
See 4 more Smart Citations
“…Otles and Yalcin analyzed phenolic compounds in root, stalk, and leaves. The authors reported the lack of gallic acid and catechin in analyzed parts of the plant [ 63 ], which is in agreement with other studies [ 16 , 17 ] but contrary to other studies that reported the presence of only gallic acid [ 11 , 64 ] or both compounds [ 19 , 61 ]. The results showed that leaves were the richest in polyphenolic compounds, followed by stalk and root [ 63 ].…”
Section: Phenolic and Polyphenolic Compounds In Stinging Nettlesupporting
confidence: 88%
“…Besides the compounds mentioned above, other phenolic acids and polyphenolic compounds were also reported in leaves but with a specific diversity because of the extraction techniques used (Table 4). Leaf [16,17] In this case, both glycosides and aglycones were reported in extracts. The presence of aglycones indicates hydrolysis during the extraction processes.…”
Section: Phenolic and Polyphenolic Compounds In Stinging Nettlementioning
confidence: 90%
See 3 more Smart Citations